Increasing Students Reading Skills Using Audio-Visual Platform with Problem-Based Learning - Yulianto , Yulianto; Rokhayati, Titi; Widiyono, Yuli (Scripta : English Department Journal, 2024)
This research aims to improve reading comprehension skills for students in eight-grade-student in Adimulyo, Indonesia. It is used YouTube video media platform and problem-based learning (PBL). Several media is used to improve students’ reading skills and YouTube is the most effective for English Narrative text. The data collection method uses observation and tests. The data analysis method is descriptive for both qualitative data and quantitative data. The results showed that before treatment using YouTube video media, the average reading comprehension score of students was 62.70 (57.70%) with the medium category. In cycle 1 was increased to 70 (69.23%), and in cycle 2 students’ was increased 81.54 (88.46%) with a very high category. The future expectation that YouTube videos can make a positive feedback for students‘ skills.